(untitled) (Raparin Journal of Humanities (RJH), 2020)
This study is about the relation between popular heritage and some humanitarian sciences such as history، sociology and enthropology، a study of man، how they move and interact with society. History is divided into two basic parts، written which is recorded by historians and oral which is narrated from one generation to another. In the ancient era، epics، lawik and hairan (special type of song related to Kurdish culture) are considered as a mirror to reflect factual and historical events. They are considered as a reliable document for popular heritage. Concerning، enthropolgy، has a great relation with the popular heritage because it is emerged from anthropology.